Mitos Ikan Terubuk dalam Syair Ikan Terubuk: : Analisis Strukturalisme Levi-Strauss - Puteri Agustefanni (Madah: Jurnal Bahasa dan Sastra, 2025)
Syair “Ikan Terubuk” exists among the people of Bengkalis but the myth of ikan terubuk doesn not. The myth is not widely known by the people. This can be seen from the phenomenon of people’s low intensity in maintaining the myth within the society. This research aims to discuss the myth of ikan terubuk in the syair of Ikan Terubuk. The syair tells a story directly related to ‘semah laut’ ritual carried out by the Bengkalis people in catching terubuk fish in the past. In addition to explaining the myth of ikan terubuk, this Malay poem also explain functions and distribution of the myth of ikan terubuk contained in the text of Syair which have developed within Bengkalis society. This research used Levi-Strauss Structuralism theory and qualitative descriptive method. The research found that the syair of Ikan Terubuk recounts the desire of terubuk fish to have princess puyu-puyu. Based on text analysis, the syair of Ikan Terubuk reflects the myth of ikan terubuk. The myth described by the author is the magical power of the syair of Ikan Terubuk in Semah Laut ritual.